Emergence of ehrlichiosis by a new tick-borne Ehrlichia species in China. (June 2023) - Lu, Miao; Qin, Xin-Cheng; Jiang, Yong-Zhong; Guo, Qian; Jin, Xiao-Jing; Teng, Zhong-Qiu; Sun, Xiang-Rong; Yu, Liang; Zhang, Yun-Fei; Wang, Wen; Chen, Qing-Qing; Liang, Jun-Rong; et al.
Highlights: A disease occurrence characterized by fever and rash was monitored in China. The etiological and epidemiological investigation was initiated. We proved that a novel species of genus Ehrlichia was its pathogen. We named the new species as " Candidatus Ehrlichia erythraense". Abstract: Objectives: From March to June 2021, the reported number of clinically diagnosed endemic typhus in Anhui and Hubei provinces of China nearly increased four-fold compared with the monthly average numbers in last 5 years. An etiological and epidemiological investigation was initiated. Methods: The clinical specimens from the reported patients and the potential vector ticks were collected for molecular and serological detection, as well as cell culturing assay to identify the potential pathogen. Results: Polymerase chain reaction and sequence analysis of rrs and groEL showed that the pathogen from these patients was Ehrlichia sp., isolated from Haemaphysalis longicornis attached to these patients. The phylogenetic analysis based on 39 Ehrlichia genomes suggested that it should be taxonomically classified as a novel species, tentatively named " Candidatus Ehrlichia erythraense". A total of 19 of 106 cases were confirmed as Candidatus Ehrlichia erythraense infections by polymerase chain reaction, sequencing, and/or serological tests. The most frequent symptoms were fever (100%), rashes (100%), asthenia (100%), anorexia (100%), and myalgia (79%). Conclusion: The occurrence of the disease presenting with fever and rashes in Anhui and Hubei provinces was caused by a novel species of the genus Ehrlichia ; physicians need to be aware of this newly-discovered pathogen to ensure appropriate testing, treatment, and regional surveillance.